KELANTAN SI 'MEKKAH KECIL': PENGARUHNYA TERHADAP PERADABAN ISLAM DI NUSANTARA (ABAD KE-15 DAN KE-19) - Erasiah, Erasiah; Surya Pratama, Fikri; Mat Zain, Farid; Syauqi Ardy, Muhammad; Dalela, Resi (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
ABSTRACT Kelantan has a historic role as the gateway to Islamic enlightenment in the archipelago. Kelantan has transformed into an area that has become a centerof Islamic learning. Together with Aceh and Patani, Kelantan is also called the 'Little Mecca'. The arrival of Islam raised Kelantan's status to be reckoned with in the world of Nusantara's Islamic cultural treasures and as a representative of the Muslim state in contemporary Malaysia. This paper aims to explorethe role of Kelantan as thegateway of Islamofthe archipelago in the 15th-19thcenturies, and its significance in the development of contemporary Islam in Malaysia. The study employedthe historical research, with the data collected throughliterature study. Data analysiswascarried out simultaneously with the process of source criticism. This was done interactively from the beginning of the research to the final stage of drawing conclusions. The results showed that the arrival of Islam brought many changes and impressions to the way of thinking andsocio-culture of the Kelantan Malay community. Kelantan Malay emerged as a civilization that developed the Islamic intellectuality of the archipelago in the 15th-19thcenturies. Kelantan also played an active role in the Islamic struggle against Western colonialism. Contemporary Kelantanese society has not lost its identity as an Islamic country under the secularism brought by the British. Kelantan has presented a positive image that Islamic law can be well accepted in a multicultural country and underthesecular government, such asthe Federation of Malaysia. Keywords: Islam in Archipelago, Kelantan, Little Mecca, Malay. ABSTRAK Kelantan memiliki peran historis sebagai pintu masuknya pence-rahan Islam ke tanah Nusantara. Kelantan bertransformasi menjadisuatu kawasan yang menjadi pusat pembelajaran agama Islam di Nusantara. Bersama Aceh dan Patani, ia adalah ‘Mekkah Kecil’ Nusantara. Kedata-ngan Islam menaikkan derajat Kelantan sebagai kekuatan yang patut diper-hitungkan dalam dunia khazanah peradabanIslam Nusantara, dan repre-sentatif Negeri Muslim di Malaysia Kontemporer. Tulisan ini bertujuan untuk menjelaskan peran besar Kelantan sebagai ‘Serambi Mekkah’ Nusan-tara pada abad ke-15-19, dan signifikansinya bagi perkembangan Islam kontemporer di Malaysia. Metode penelitian yang digunakan adalah metode penelitian sejarah, dengan teknik pengumpulan data yang digunakan adalah studi pustaka. Proses analisa data penelitian dilakukan serentak dengan proses kritik sumber. Hal ini dilakukan secara interaktif sejak awal pene-litian hingga tahap terakhir pengambilan kesimpulan. Hasil penelitian menunjukkan bahwa kedatangan Islam telah banyak membawa perubahan dan kesan kepada corak berpikir serta sosio-budaya masyarakat Melayu Kelantan. Melayu Kelantan tampil sebagai peradaban yang mengembang-kan keintelektualan Islami Nusantarapada abad ke-15-19. Kelantan juga berperan aktif dalam perjuangan jihad Islam melawan penjajahan Barat. Masyarakat Kelantan kontemporer tidak kehilangan jati diri mereka sebagai negeri Islam di semenanjung di bawah gempuran sekulerisme yang dibawa Inggris. Kelantan menunjukkan citra positif bahwa hukum Islam dapat diterima dengan baik dalam negeri yang multikultural, serta menjadi repre-sentasinegeri berhukum Islam kaffah di bawah pemerintahan Federasi Malaysia yang sekuler. Kata kunci: Islam di Nusantara, Kelantan, Mekkah Kecil, Melayu, Serambi Mekkah.